Analisis Terhadap Tingginya Nikah Siri Di Kabupaten Pamekasan - Sufyan, Akhmad Farid Mawardi (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2019)
Ikatan Perkawinan mempunyai arti penting dalam kehidupan manusia. Seiring dengan perkembangannya karena sah dan tidaknya suatu perkawinan sesuai dengan agamanya maka kawin siri sangat marak dan menjadi ngetrend. Ini adalah penelitian normatif - lapangan.Â  Menurut UU. No. 1/1974,Â  Perkawinan adalah sah apabila dilakukan menurut hukum masing-masing agamanya dan kepercayaannya itu. Faktor utama dilakukan nikah siri karena ketidafahaman & pola pikir masyarakat di Kabupaten Pamekasan terhadap pentingnya perkawinan yang dicatatkan, fungsi serta akibat hukum yang timbul di masa mendatang. Pemkab Pamekasan bersama perangkat Kantor Urusan Agama menyelenggarakan program nikah massal secara ekonomis sebagai solusi menekan angka nikah siri. (Marriage ties have an important meaning in human life. Along with its development because it is legal and whether a marriage is in accordance with its religion, siri marriage is very lively and becomes popular. This is normative - field research. According to the law. No. 1/1974, Marriage is legal if it is done according to the law of each of its religions and beliefs. The main factor is the marriage of siri because of the misunderstanding & mindset of the people in Pamekasan Regency regarding the importance of registered marriages, functions and legal consequences that arise in the future. Pamekasan Regency Government together with the Office of Religious Affairs organizes a mass marriage program economically as a solution to reduce the number of siri marriageÂ